2014
DOI: 10.1155/2014/481016
|View full text |Cite
|
Sign up to set email alerts
|

Light and Darkness: Prevalence of Hepatitis E Virus Infection among the General Population

Abstract: Human hepatitis E virus (HHEV) spreads early in life among the population in areas endemic for genotype 1 and infects mainly adults in areas endemic for genotype 3, where it would be responsible for about 10% of cases of suspected acute viral hepatitis of unknown etiology and for a number of subclinical, unrecognized infections. The overall prevalence of antibody to HHEV is high in most of the former areas and low in most of the later ones, but wide regional differences have been recorded in both cases. “Hot s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 105 publications
0
29
1
9
Order By: Relevance
“…A wide range of clinical manifestations, from asymptomatic or subclinical to acute liver failure, can be observed [15]. The current rate between infection and disease is still unknown, but it is accepted that asymptomatic infection is the most common scenario [16]. The data from an outbreak on a cruise ship caused by genotype 3 showed that 67% of the infected people were asymptomatic [17].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of clinical manifestations, from asymptomatic or subclinical to acute liver failure, can be observed [15]. The current rate between infection and disease is still unknown, but it is accepted that asymptomatic infection is the most common scenario [16]. The data from an outbreak on a cruise ship caused by genotype 3 showed that 67% of the infected people were asymptomatic [17].…”
Section: Introductionmentioning
confidence: 99%
“…Also, in Portugal, a case control study and different studies have shown the anti-HEV IgG prevalence of 2.1% -29% that was due to the different specificities and sensitivities of the assay (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…This was the case of a hepatitis E outbreak that took place in 2008 during a cruise [91]. The concept of hepatitis E as a food-borne disease is particularly strong in western Europe, where the food chain is the main source of infection [92].…”
Section: Transmission Routesmentioning
confidence: 99%